Toxic Ingestion/Ethylene Glycol Ingestion - Mary Wittler; Mary Claire O'Brien (Association of American Medical Colleges, 2015)
Abstract Introduction Ethylene glycol overdose is an infrequent but potentially life-threatening ingestion that requires critical thinking and immediate interventions to prevent patient demise. As this is a less frequently encountered ingestion, most residents and fellows were not familiar with its management. This simulation case reviews the toxicity from ethylene glycol ingestion. Methods The resource contains a case narrative, which includes all pertinent case information, interpretations of the case information, and anticipated case branch points. The resource also contains a PowerPoint with pertinent case lab information, the X-ray, and the EKG to be used during the case simulation. A debriefing PowerPoint that reviews teaching points for ethylene glycol toxicity and an evaluation form are also included. Results This case has been used numerous times for group simulation training. Additionally, the case content has been used more than 20 times as an oral board type case. Discussion During the case deployment, residents and fellows used this case to identify gaps in their knowledge base, critically evaluate care decisions for this complex medical scenario, improve their familiarity with the case management, and discuss nuances of antidote administration.